Association between occupational lifting and day-to-day change in low-back pain intensity based on company records and text messages - Andersen, Lars Louis; Fallentin, Nils; Ajslev, Jeppe Zielinski Nguyen; Jakobsen, Markus Due; Sundstrup, Emil (Scandinavian Journal of Work, Environment & Health, 2017)
' ' OBJECTIVE ': 'This study aimed to investigate the association between occupational lifting and day-to-day change in low-back pain (LBP) intensity. ' ' METHODS ': 'Each day for three consecutive weeks, 95 full-time workers from 51 Danish supermarkets with frequent occupational lifting replied to daily text messages about LBP intensity (scale 0–10). Supervisors at the supermarkets provided information about daily working hours and load (number of different pallets handled) for each worker during the three weeks. Linear mixed models with repeated measures tested the association between variables controlled for LBP during the previous day and various confounders. ' ' RESULTS ': 'Workers handled on average 1212 [standard deviation (SD) 861] kg and worked 8.5 (SD 1.8) hours per workday. LBP intensity was higher in the morning after work- compared with non-workdays [difference of 0.55, 95% confidence interval (95% CI) 0.39–0.71]. A cumulative effect of consecutive workdays existed, ie, pain intensity increased approximately 0.30 points per day for up to three days. For three consecutive work- compared with non-workdays, the difference was 0.92 (95% CI 0.50–1.34). Higher load resulted in higher pain intensity in the morning after workdays [0.16 (95% CI 0.02–0.31) per ton lifted], while no effect was found for number of daily working hours. ' ' CONCLUSION ': 'Among workers with frequent occupational lifting, workdays are associated, in a cumulative manner, with increased LBP intensity. Furthermore, an exposure–response association exists between workload and increased LBP intensity. However, the increase in pain intensity was small and future studies should assess whether long-term consequences exist.
Keywords: back pain; company record; exposure–response; low-back pain; musculoskeletal disorder; occupational lifting; pain; pain intensity; physical workload; SMS; text message